Designing Applications For Dictionary Of Indonesian Law Based On Android - Arlin Nurliyani (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2019)
There is no legal dictionary application and to answer this, the mobile legal dictionary application is created. Indonesian law dictionary-based Android is an application that provides information about the law in Indonesia. This dictionary contains information such as Pancasila law, the Constitution of 1945, the terms of the law in Indonesia, the Book of Law - Criminal Code, and the Book of Civil Law Act. The application also comes with a memo that can be used to record. System development methodology in Indonesia this law dictionary application using RUP methodology (Rational Unified Process) which is a development system using a model of UML (Unified Model Language). This application is made by using a system that supports the application of the Eclipse ADT (Android Development Tools) which is an eclipse plugin that connects IDE and Android SDK. From testing the application, the application's performance can be used according to its functions and needs.